Institutionalisation aspects in the use of geographic information system (GIS) - Mohd. Hussain, Mohd. Ramzi (UM, 2011)
The paper explains the institutionalisation aspects associated with the utilisation of GIS in an organisation. Studies of technology in organisations have demonstrated the value of treating information technologies as human artefacts with social constructed meanings. Simultaneously, the human agency has the potential to revise both the information systems and the social context within which the technology is used. Given these circumstances, this paper focuses on the institutionalisation aspects between individual and organisational factors in utilising GIS. These aspects are important in order to recognise patterns in the way GIS is implemented and used. The study identified five set of institutionalisation aspects that governed the effective use of GIS in organisation. They are the organisational context, the personalities of the individual involved, the impact of change and instability, centralisation and decentralisation of computing technology in organisation and the state of computing development. The paper combines an overview of institutionalisation aspects and their relationship to GIS with examples of strategies adopted by organisations to handle this aspect of system development. The overview provides framework from the subsequent literature concerning the implementation of information technology in general and applying this to the utilisation of GIS. Therefore, the paper provides a more interesting and insightful perspective of the utilisation of information such as GIS in organisations.